(untitled) (Journal of Life and Earth Science, 2014)
Landscape of Dhaka city, one of the fastest growing mega cities in the world, is undergoing continuous changes and modifications due to unplanned hasty urbanization process. As the growth of urbanization taking place at an exceptionally rapid rate the city is unable to cope with changing situation due to internal resource constraints and management limitations. Dhaka city endowed with a large number of water-bodies both big and small, which includes river, khals, lakes, flood plain low-lying areas etc. However, pre and post-urban changes of water-bodies in the city were studied using topographic map of 1960 and a satellite image of 2008 (ALOS VNIR 2008) through GIS and remote sensing technique. It is found that in 1960 total areas of water-bodies and lowland were 2952.02 and 13527.58 hectares. But in 2008 total areas of water-bodies and lowland found 1990.71 and 6414.57 hectares. Categories (water-bodies and lowlands) of wetland areas were decreased harshly. Study shows that water-bodies and lowland areas were decreased 32.57% and 52.58% that means more than 49% of the wetland areas decreased over the period 1960 to 2008. The changes of low-lying areas in the south-western corner extending towards Mirpur, Muhammadpur and Pallabi-Cantonment areas and filled for the urban development. The part of Gulshan and Dhanmondi lakes has also been reduced; and some of the channels of Motijheel areas are not identifiable at present. The growth of urban infrastructures have been taking place in unplanned way; as a result it destroyed natural drainage systems, fill-up the water-bodies, causing water-loggings during rainy season in various part of the city. This study revealed that immediate necessary steps should take by concern authority to prevent from various disasters that might be occurred due to unwise and unplanned wetland changes. DOI: http://dx.doi.org/10.3329/jles.v7i0.20126 J. Life Earth Sci., Vol. 7: 83-90, 2012